Fine Structure of Succinate-Swollen Rhizobium trifolii 0403 - Urban, James E. (1984)
Transmission electron micrographs of glutaraldehyde- OsO(4)-fixed Rhizobium trifolii 0403 before and after cells were treated with 16.6 mM succinate showed that treated cells increased in mass by increasing cytoplasmic volume. The morphology of succinate-treated cells was identical to that of bacteroids, and the appearances of the envelope and periplasmic space were similar. The primary difference was in inclusion number and type.